Samochód jako wyzwanie dla miasta XXI wieku = Car as a challenge for 21st century city - Zając, Adam Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Increasing number of cars in urban areas is becoming bigger problem in many developed countries. Popularization of private cars in cities caused redevelopment of urban area, which has mainly focused on adapting space to needs of car owners.
Keywords: miasto; samochód; transport zbiorowy; zagospodarowanie przestrzeni; mobilność; socjologia transportu; jakość życia; city; car; public transport; land-use; mobility; sociology of transport; quality of life